Protesting Against Gender-Based Violence: Narratives on The Silent Protest and #RUReferenceList - Mhlangulana, Aphiwe (Department of Psychology, 2024)
Abstract Gender-based violence (GBV) has been a problem in South African higher education institutions (HEIs) for many years. International research suggests that sexual violence is more prevalent in university campuses than in public. As a response to the prevalence of GBV in HEIs, students held several protests between 2015 and 2016 bringing the discussion of GBV prevalence in South African HEIs back into the spotlight. However, there is a gap in literature that studies the experiences of student activists in protests against GBV with little to no literature on the identities of those who took part in these protests, and how their participation was shaped by their identities and experiences. Therefore, informed by a feminist intersectional perspective this project seeks to study the narratives of participants of the Silent Protest and the #RUReferenceList protests that took place at the University Currently Known as Rhodes (UCKAR). The project aims to contribute to an intersectional understanding of the experiences of students who participate in protests against gender-based violence and the motivations for their participation in the protests. The co-researchers in the project are persons who participated in either the Silent Protest, the #RUReferenceList protest, or both. Data was collected through in-depth interviews with five participants of the two protests, as well as a review of archival material related to the protests. All the data were analysed using the Decolonial Intersectional Narrative Analysis tool. Through studying the participants' experiences, we can begin to understand the motivations behind protests against gender-based violence and the effects of protests against gender-based violence on those who participate in them.